Regret Aversion in Reason-based Choice - CONNOLLY, Terry (Institutional Knowledge at Singapore Management University, 2011)
This research examines the moderating role of regret aversion in reason-based choice. Earlier research has shown that regret aversion and reason-based choice effects are linked through a common emphasis on decision justification, and that a simple manipulation of regret salience can eliminate the decoy effect, a well-known reason-based choice effect. We show here that the effect of regret salience varies in theory-relevant ways from one reason-based choice effect to another. For effects such as the select/reject and decoy effect, both of which were independently judged to be unreasonable bases for deciding, regret salience eliminated the effect. For the most-important attribute effect that is judged to be normatively acceptable, however, regret salience amplified the effect. Anticipated self-blame regret and perceived decision justifiability consistently predicted preferences and thus offer a parsimonious account of both attenuation and amplification of these reason-based choice effects.